Atividade de produtos fitossanitários naturais sobre Anticarsia gemmatalis hübner (Lepidoptera: Noctuidae), Bacillus thuringiensis subesp. kurstaki e seletividade a Apis mellifera L. (Hymenoptera: Apidae) - Vilani, Andréia (2013)
Knowing the effects of natural products phytosanitary (NPP) on pests and organisms target is not essential in the context of Integrated Pest Management. This study aimed to evaluate the activity of PFN on Anticarsia gemmatalis Hubner (Lepidoptera: Noctuidae), spores and crystals of Bacillus thuringiensis subsp. kurstaki (Btk) and selectivity of Apis mellifera L. (Hymenoptera: Apidae). We used extracts of cherry (Eugenia uniflora), pepper (Capsicum baccatum var. pendulum), trumpet (Brugmansia suaveolens) and Blueberry japan (Hovenia dulcis), to 5%, Natuneem®, Natualho®, Pironat®, Rotenat® Bordeaux and Syrup (SB), the concentration recommended by the manufacturer. For spores, the treatments Btk + NFP and Btk alone were incubated on horizontal shaker (150 rpm, 30 ± 2 ° C, 2 h) and inoculated onto nutrient agar plates (NA), in petri dishes. We prepared four plates (repetitions), placed in a climatic chamber (30 ± 2 º C, 18 h), quantifying the colony forming units (CFU) / mL. To crystals, the PFN and Btk alone sterilized distilled water (control) and Btk + NFP after incubation under the conditions described above were applied on artificial diet cubes for A. gemmatalis, in Petri dishes, which received 20 second instar larvae of each. We prepared four plates (repetitions), placed in a climatic chamber (26 ± 2 º C, RH 70% ± 10% photophase 14 h), evaluating mortality after 24, 48, 72, 96 and 120 h, the percentage empupament and the emergence and egg-adult period. The selectivity of A. mellifera was evaluated by spraying treatments on workers and adding them to pasta Candi. As a control we used respectively sterile distilled water and paste Candi pure. In both experiments, we used 30 workers per treatment (repeat), individually in glass tubes (10 cm × 2.5 cm), packed in a climatic chamber (25 ± 2 ° C, RH 70% ± 10%, photophase 12 h) mortality, assessed by one, two, three, four, five, six, nine, 12, 15, 18, 21, 24, 30, 36, 42, 48, 60, 72 and 96 h. It was found that the extracts of cherry, pepper and Blueberry japan significantly reduced CFU / mL. The cherry extract was the only negatively affecting toxicity of Btk crystals. No plant extract affected the mortality, there was no difference between the time of evaluation, nor empupament, emergence and egg-adult period. In mixture with Btk cherry extract delayed the mortality and pepper extract accelerated mortality. In experiments with A. mellifera, was significantly reduced only to extract Blueberry japan, when sprayed. Natuneem® products and Rotenat® were the only ones who have significantly increased CFU / mL. Only the SB negatively affected the toxicity of Btk crystals. Ns other parameters, there was significant reduction in the percentage of empupament for SB and Natualho® and percentage of emergency and SB Natuneem®. Between the time of evaluation, no influence of individual products, the mix with Btk Natualho®, Pironat®, Rotenat® accelerated mortality and SB negatively influenced. There was no activity of the products on the egg-adult period. To A. mellifera, in both experiments, the products did not significantly affect longevity.